The impact of age of onset on amygdala intrinsic connectivity in major depression - Clark DL (Dove Medical Press, 2018)
Darren L Clark,1–4 Nithya Konduru,1 Anne Kemp,5 Signe Bray,6–8 Elliot C Brown,1–4 Bradley Goodyear,1,2,4,6 Rajamannar Ramasubbu1–4 1Department of Psychiatry, 2Department of Clinical Neuroscience, 3Mathison Centre for Mental Health Research and Education, 4Hotchkiss Brain Institute, University of Calgary, Calgary, 5School of Medicine, University of Alberta, Edmonton, 6Department of Radiology, 7Department of Pediatrics, University of Calgary, 8Child and Adolescent Imaging Research Program, Alberta Children’s Hospital, Calgary, AB, Canada Background: Early-onset major depressive disorder (EO-MDD), beginning during childhood and adolescence, is associated with more illness burden and a worse prognosis than adult-onset MDD (AO-MDD), but little is known about the neural features distinguishing these subgroup phenotypes. Functional abnormalities of the amygdala are central to major depressive disorder (MDD) neurobiology; therefore, we examined whether amygdala intrinsic connectivity (IC) can differentiate EO-MDD from AO-MDD in a cohort of adult MDD patients.Subjects and methods: Twenty-one EO-MDD (age of onset ≤18 years), 31 AO-MDD patients (age of onset ≥19 years), and 19 healthy controls (HCs) underwent resting-state functional magnetic resonance imaging (7 minutes). Amygdala seed-based resting-state functional connectivity was compared between groups.Results: AO-MDD patients showed loss of inverse left amygdala–left dorsolateral prefrontal cortex IC and increased inverse left amygdala–left inferior parietal IC, compared to both HCs and EO-MDD. EO-MDD showed a switch from inverse to positive IC with right dorsomedial prefrontal cortex, compared to HCs and AO-MDD. This effect was removed when we controlled for illness burden.Conclusion: Alterations in amygdala IC with the default-mode network were specifically related to EO-MDD, whereas amygdala IC with executive cognitive control regions was preferentially disrupted in AO-MDD. Increased illness burden, an important clinical marker of EO-MDD, accounted for its specific effects on amygdala IC. Brain imaging has the potential for validation of clinical subtypes and can provide markers of prognostic value in MDD patients. Keywords: major depressive disorder, onset age, resting-state functional connectivity, functional magnetic resonance imaging, biomarker, amygdala